2020
DOI: 10.1002/fsn3.1457
|View full text |Cite
|
Sign up to set email alerts
|

Changes in starch structures and in vitro digestion characteristics during maize (Zea mays L.) germination

Abstract: This study analyzed changes in the starch structures and in vitro digestion profiles of a specific maize cultivar, Jike 728 (JK728), in Jilin, China, after 0–5 days of germination. The total starch, amylose, and amylopectin contents decreased significantly during germination. The average molecular weight of the starch compounds also decreased significantly during germination. The proportion of amylopectin with a degree of polymerization (DP) of 13–24 significantly decreased, while the relative abundance of amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The reduced starch content in R7954 agreed with other reports that during the germination process of brown rice, starch was broken down by activated hydrolytic enzymes which led to the increased digestibility and reduced total starch content (Wu et al, 2013). Ma et al (2020) found germinated maize had significantly reduced RS. And the RS content of waxy rice decreased from 7.1% to 3.1% after germination (You et al, 2016).…”
Section: Total Starch Rs and Total Amylase Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…The reduced starch content in R7954 agreed with other reports that during the germination process of brown rice, starch was broken down by activated hydrolytic enzymes which led to the increased digestibility and reduced total starch content (Wu et al, 2013). Ma et al (2020) found germinated maize had significantly reduced RS. And the RS content of waxy rice decreased from 7.1% to 3.1% after germination (You et al, 2016).…”
Section: Total Starch Rs and Total Amylase Activitysupporting
confidence: 90%
“…Ma et al . (2020) found germinated maize had significantly reduced RS. And the RS content of waxy rice decreased from 7.1% to 3.1% after germination (You et al., 2016).…”
Section: Resultsmentioning
confidence: 98%
“…In vitro digestibility of native and OSA-modified starches was analyzed according to the method of Ma et al [26]. Briefly, samples were suspended in a sodium acetate buffer, and the mixture was heated at 95 • C for 30 min.…”
Section: In Vitro Digestibility Assaymentioning
confidence: 99%
“…In vitro digestibility of the rice starches was tested according to the method of X. H. Ma et al (2020). Briefly, the starch sample was suspended in a sodium acetate buffer and the mixture was heated at 95°C for 30 min.…”
Section: In Vitro Starch Digestibility Assaymentioning
confidence: 99%